Lexical cohesive devices in the texts from esp course book “English For Economics” by assoc. Prof. Nguyễn Xuân Thơm, phd. And pedagogical implications for teaching esp to third year students at felte, ulis, vnu. = Phương tiện liên kết văn bản trong sách giáo trình “English For Economics” cho sinh viên năm 3, Khoa SPTA, HNN, HQGHN. - Đỗ, Hà Phương (2021)
This study analyzes lexical cohesive devices to see how often they appear in Business English course book, from which conclusions are made for both teachers and students in hopes of improving reading economic texts skill and broadening specialized vocabulary. The description of data was adopted from the taxonomy of cohesion by Halliday and Hasan (1976). The data for analysis were taken from five reading texts in the course book English for Economics by Assoc. Prof. Nguyễn Xuân Thơm (PhD.). After data collection, analysis and statistic were implemented, and the results of the study were compared within the text. The results revealed that all types of lexical cohesive devices found in the BE sample texts at different rates all contributed to the text cohesion; and of all the cohesive devices, repetition is used most frequently. At the end of the study, some implications for teaching and learning BE have been made in context of ULIS.